Penyuluhan Penetapan Harga Pokok Produksi Barang/Jasa Bagi Anggota AMPI/HKTI Bandung Barat - Novyarni, Nelli; Anhar, Muhammad; Sumitro, Sumitro; Maserih, Maserih (Universitas 17 Agustus 1945 Jakarta, 2024)
ABSTRACT The aim of this community service is to provide an understanding of how to determine the basic production price of cow's milk products for dairy farmers in Pengalengan and to provide an understanding of marketing strategies for cow's milk products for dairy farmers in Pengalengan. The method used is interactive where the speaker and participants ask each other questions and answers regarding the counseling given. The result of this community service is that the participants understand how to calculate the cost of production for goods and services sold in the form of cow's milk and agricultural products such as potatoes and vegetables. The implication of this community service is the application of the correct calculation of the cost of production for livestock breeders and farmers in canning so as to produce competitive selling prices.